2017
DOI: 10.1002/mus.25580
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem reflex excitability changes in patients with amyotrophic lateral sclerosis

Abstract: Brainstem inhibitory and excitatory interneuronal activity is altered in ALS, possibly brought about by physiological and morphological changes at the cortical or bulbar levels. Muscle Nerve 56: 925-929, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Using the discharge rate method, we found that the electrical lip stimulation only generates a long-lasting single or compound inhibitory response that is followed by a late, long-lasting excitation in the masseter motor units. These findings have important implications on the redrawing of the neuronal pathways of the trigeminal nerve that are frequently used to judge neuromuscular disorders of the trigeminal region (Cengiz et al 2017;İnan et al 2017). Moreover, it is clinically important to elucidate the nature of the changes in bite force during electrical lip stimulation, because it represents the response of the entire masticatory system to painful intraoral impacts that can occur accidently in everyday life during eating.…”
Section: Discussionmentioning
confidence: 99%
“…Using the discharge rate method, we found that the electrical lip stimulation only generates a long-lasting single or compound inhibitory response that is followed by a late, long-lasting excitation in the masseter motor units. These findings have important implications on the redrawing of the neuronal pathways of the trigeminal nerve that are frequently used to judge neuromuscular disorders of the trigeminal region (Cengiz et al 2017;İnan et al 2017). Moreover, it is clinically important to elucidate the nature of the changes in bite force during electrical lip stimulation, because it represents the response of the entire masticatory system to painful intraoral impacts that can occur accidently in everyday life during eating.…”
Section: Discussionmentioning
confidence: 99%
“…In CP, such changes in neuronal excitability can result from direct damage to the brain stem. In other neurological conditions where there is direct damage to the brain stem, as occurs in amyotrophic lateral and multiple sclerosis, there is a decrease in inhibitory masseter reflexes, augmentation of excitatory blink reflexes (Cengiz et al 2017), and a delayed latency of various other brain stem reflexes, including the TCR (Magnano et al 2014). Given that the brain stem in CP can show decreases in mean volume (Kułak and Sobaniec 2007) and fractional anisotropy (Mu et al 2014), alterations in TCR excitability shown in this study may arise from direct damage to brain stem structures.…”
Section: Hyperexcitable Scm Tcrs In Cpmentioning
confidence: 99%
“…Reflexes evoked from trigeminal afferent stimulation (cranial nerve V) have been used to assess brain stem damage in several neurological disorders (Cengiz et al 2017;Di Lazzaro et al 1996;Magnano et al 2014;Serrao et al 2011). In humans, the shortlatency (~13 ms) component of the trigeminocervical reflex (TCR) is thought to have a similar pathway to that in the cat (Manni et al 1975;Nishimura et al 1992) whereby afferents from the trigeminal nerve synapse in the rostral portion of the spinal trigeminal nucleus in the pons (Di Lazzaro et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In this assessment, stimulation response to mandibular nerves is recorded with EMG of the jaw muscles. Nerve stimulation is known to elicit two periods of muscle silence: first or early component reflecting the shorter oligosynaptic spinal pathway and the second reflecting the longer or long-loop transcortical reflex [4]. Latencies and durations of the silent periods are able to reveal the excitability of the brainstem and the sensorimotor system.…”
mentioning
confidence: 99%